Clinical and experimental studies of a novel P525R FUS mutation in amyotrophic lateral sclerosis. (August 2017) - Kuang, Lisha; Kamelgarn, Marisa; Arenas, Alexandra; Gal, Jozsef; Taylor, Deborah; Gong, Weiming; Brown, Martin; St. Clair, Daret; Kasarskis, Edward J.; Zhu, Haining
Abstract : Objective: To describe the clinical features of a novel fused in sarcoma (FUS) mutation in a young adult female amyotrophic lateral sclerosis (ALS) patient with rapid progression of weakness and to experimentally validate the consequences of the P525R mutation in cellular neuronal models. Methods: We conducted sequencing of genomic DNA from the index patient and her family members. Immunocytochemistry was performed in various cellular models to determine whether the newly identified P525R mutant FUS protein accumulated in cytoplasmic inclusions. Clinical features of the index patient were compared with 19 other patients with ALS carrying the P525L mutation in the same amino acid position. Results: A novel mutation c.1574C>G (p.525P>R) in the FUS gene was identified in the index patient. The clinical symptoms are similar to those in familial ALS patients with the P525L mutation at the same position. The P525R mutant FUS protein showed cytoplasmic localization and formed large stress granule–like cytoplasmic inclusions in multiple cellular models. Conclusions: The clinical features of the patient and the cytoplasmic inclusions of the P525R mutant FUS protein strengthen the notion that mutations at position 525 of the FUS protein result in a coherent phenotype characterized by juvenile or young adult onset, rapid progression, variable positive family history, and female preponderance.